2010
DOI: 10.3109/00016489.2010.502185
|View full text |Cite
|
Sign up to set email alerts
|

Rib cartilage harvesting in rhinoplasty procedures based on CT radiological data

Abstract: On both sides, the seventh rib was identified as the most cartilage-containing rib, independent of gender. The length of costal cartilage of the sixth and seventh rib was significantly related to age on both sides (p < 0.01). This finding did not reach statistical significance for the eighth rib, on either the right (p = 0.376) or the left side (p = 0.204). Calcification of the sixth and seventh rib, but not of the eighth rib, significantly increased with age. In general, calcification was not related to gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Recently, Kim et al 9 harvested the 10th costal cartilage with only a 1-cm incision and used it in a columella strut and tip onlay graft.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recently, Kim et al 9 harvested the 10th costal cartilage with only a 1-cm incision and used it in a columella strut and tip onlay graft.…”
mentioning
confidence: 99%
“…Lack of septum structures may require cartilage grafts from the ear [358] or rib [389]. A height of at least 3 cm has to be considered for this procedure [357].…”
Section: Discussionmentioning
confidence: 99%
“…Right side cartilages are commonly preferred than the left to avoid injury to the pericardium and confusion of postoperative chest pain from angina [1][2][3][4][5][6][7][8][9] . Interestingly, however, a study revealed that the greatest amount of costal cartilage from the sixth, seventh, and eighth rib was identified on the left side than right on CT scan data [10] . Therefore, rib cartilage harvesting from the left side can be a viable option in those patients who have had previous rib surgery, radiotherapy, or trauma with destruction of costal cartilage on the right side [10] .…”
Section: Decision To Use a Rib: Consideration Factorsmentioning
confidence: 98%